Analisis Transformasi Brosur PMB Universitas PGRI Wiranegara (Kajian Multimodal) - Maknun, luluul; Mardiningsih, Mardiningsih; Sugianti, Sugianti (Universitas Negeri Padang, 2025)
This research aims to reveal the transformation of content and visuals in the New Student Admission (PMB) brochure of Universitas PGRI Wiranegara (UNIWARA) from 2020 to 2025 using a multimodal analysis approach. This approach is based on the theory of Kress and Van Leeuwen (2006), which divides multimodal elements into three metafunctions: representational, interactive, and compositional. The research method used is qualitative descriptive, with documentary techniques and content analysis of five editions of the PMB brochure. The results show that there has been a significant change in message delivery strategies through the transformation of visual, verbal, and compositional elements. These transformations reflect the institution's response to the dynamics of higher education promotion and changing preferences of prospective students. The multimodal elements work together to create a more persuasive, informative, and inclusive institutional image.